Treatment of Furcal Perforation of Primary Molars with ProRoot MTA versus Root MTA: A Laboratory Study - Haghgoo, Roza; Abbasi, Farid (Iranian Endodontic Journal, 2013)
Introduction: Furcal perforations are one of the most challenging causes of endodontic failures. Several materials including MTA have been used for non surgical repair of these perforations. The aim of this study was to compare treatment outcome of furcal perforation treatment in primary molars using Root MTA and ProRoot MTA. Materials and Methods: This in vitro study was conducted on 54 primary first molars that were randomly divided into the two experimental groups of 24 teeth each and two control groups (n=6). After preparation of access cavities, perforations were made and the perforation areas were repaired using either Root or ProRoot MTAs. After staining and preparation of mesiodistal longitudinal sections, dye leakage was measured using a stereomicroscope. The data was analyzed by the Mann Whitney statistical test. Significant level was set at 0.05. Results: The data indicated that the dye leakage of ProRoot MTA is significantly lesser than Root MTA (P=0.001). Conclusion: ProRoot MTA showed good sealing ability in repairing furcal perforations of primary molars.